Self-monitoring of oral anticoagulation: does it work outside trial conditions?. Issue 2 (29th January 2009) - Gardiner, C; Longair, I; Pescott, M A; Erwin, H; Hills, J; Machin, S J; Cohen, H
Abstract : Background: Patient self-monitoring (PSM) of oral anticoagulation therapy (OAT) can improve anticoagulant control, but poor uptake and high dropout rates have prompted suggestions that PSM is suitable for only a minority of patients in the UK. Aims: To determine whether PSM could be a viable alternative to regular hospital anticoagulant clinic attendance, if offered from the start of treatment. Methods: 318 consecutive patients referred, for the first time, to an anticoagulation clinic were assessed for eligibility using established criteria. Patients electing for PSM attended training and, following successful assessment, performed a capillary blood INR every two weeks or more frequently if directed to do so by the anticoagulation clinic. Primary outcome measures were uptake of PSM and the percentage time in target therapeutic INR range (TIR) compared to patients electing for routine clinic care. Results: Of 318 patients referred for OAT, 188 were eligible for PSM. 84 (26%) elected to self-monitor, of whom 72 (23%) remained self-monitoring or had completed their course of treatment at the end of the audit. Self-monitoring patients had significantly better anticoagulant control than those receiving routine hospital anticoagulation clinic care (TIR 71% vs 60%, p = 0.003) and significantly less time outside critical limits, ie, INR <1.5 or >5.0 (0.45% vs 2.04%, p = 0.008). Conclusions: Patients offered PSM from the start of treatment show increased uptake compared to previous UK studies and a level of oral anticoagulation control comparable to that reported in previous clinical trials.